Impartial Third-Party Interventions in Captive Chimpanzees: A Reflection of Community Concern - von Rohr, Claudia Rudolf; Koski, Sonja E.; Burkart, Judith M.; Caws, Clare; Fraser, Orlaith N.; Ziltener, Angela; van Schaik, Carel P. (PLOS ONE, 2012)
Because conflicts among social group members are inevitable, their management is crucial for group stability. The rarest and most interesting form of conflict management is policing, i.e., impartial interventions by bystanders, which is of considerable interest due to its potentially moral nature. Here, we provide descriptive and quantitative data on policing in captive chimpanzees. First, we report on a high rate of policing in one captive group characterized by recently introduced females and a rank reversal between two males. We explored the influence of various factors on the occurrence of policing. The results show that only the alpha and beta males acted as arbitrators using manifold tactics to control conflicts, and that their interventions strongly depended on conflict complexity. Secondly, we compared the policing patterns in three other captive chimpanzee groups. We found that although rare, policing was more prevalent at times of increased social instability, both high-ranking males and females performed policing, and conflicts of all sex-dyad combinations were policed. These results suggest that the primary function of policing is to increase group stability. It may thus reflect prosocial behaviour based upon “community concern.” However, policing remains a rare behaviour and more data are needed to test the generality of this hypothesis.